The genealogy of the sublation idea by blind people in Brazil: a study based on L. S. Vygotski - Bento Selau; Rafael Fonseca de Castro (Editora da Universidade de Santa Cruz do Sul, 2018)
This study aims to discuss the concept of sublation. It was originated from the graduation of blind people in higher education in Brazil, based on students' reports and on L. S. Vygotski's work. The qualitative investigation that supported this study was carried out as case studies. Nine blind people who had finished their college education were taken as subjects. Data were collected by interviews and document analysis (essays), underwent the procedures of discourse textual analysis. Results show that the concept of dialectic sublation proposed by Vygotski - based on Hegel - focuses on enhancing the blind with the use of cultural tools of mediation: in the case of the participants of the study, their interest in learning scientific concepts was the greatest ally to sublate blindness. Further recommendations comprise the fact that sublation involving the education of the blind, must be promoted with the support of collective pedagogical work.